Raman spectroscopy as a non‐invasive technique for the quantification of melanins in feathers and hairs. (12th August 2013) - Galván, Ismael; Jorge, Alberto; Ito, Kazuma; Tabuchi, Keisuke; Solano, Francisco; Wakamatsu, Kazumasa
Summary: The quantification of melanins is a complex task due to the chemical heterogeneity of the pigments and the difficulty of their isolation. The best accepted procedure currently consists in the chemical cleavage of melanins and the subsequent detection of degradation products by HPLC, which implies the destruction of samples. Here, we show that Raman spectroscopy is a non‐invasive technique that can be used to quantify melanins. We made parallel analyses of the characteristics of pheomelanin and eumelanin Raman spectra as measured by confocal Raman microscopy and of degradation products of pheomelanin (4‐amino‐3‐hydroxyphenylalanine, 4‐AHP) and eumelanin (pyrrole‐2, 3, 5‐tricarboxylic acid, PTCA) as measured by HPLC in feathers of red‐legged partridges and hairs of wild boars and humans. We found strong correlations between the spectral Raman characteristics and 4‐AHP and PTCA levels, which indicates that the Raman spectra of melanins can be used to determine their content.